Innovation of Shopping Bags Made from Patchwork as Provision for Women's Skills in Bandung Village Rt 01 Rw 05 Gedeg District, Mojokerto Regency - Sudarti Sudarti; Oktania Putri Angelina; Sherly Nur Laili (Unram Journal of Community Service, 2022)
Garbage is used goods obtained from human and natural activities that have no economic value. Until now, waste is still an unresolved problem, one of which is in Indonesia. Patchwork is the remnants of cutouts from fabric-making or convection businesses. The abundance of patchwork potential is not proportional to the processing carried out. The tailors or workers on average do not know the importance of patchwork processing so the patchwork is discarded without being reprocessed. This problem also occurs in Bandung Village. The high level of use of plastic waste can be minimized by utilizing the potential of patchwork through shopping bags made of patchwork (Patchwork Bag). The purpose of this study was to provide education about the importance of making shopping bags made of patchwork and to improve the skills of women in making shopping bags made of patchwork. The research method used is a qualitative description. The results showed that the women in Bandung Village were very happy with the training activities to make shopping bags made of patchwork. This can provide additional insight, improve skills, and can be used for entrepreneurs.